Parents' perspective on sociocultural beliefs and practices contributing to delayed health seeking by adolescents with cryptorchidism presenting at a selected in Tshwane - Bhana-Pema, Varshika (University of Pretoria, 2023)
Dissertation (MCur (Nursing Science))--University of Pretoria, 2023.